Konsumsi Kopi Jenis Arabika dan Robusta pada Penderita Asam Urat - Marisa; Rinda Lestari (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
Uric acid is the last metabolite of purines, which is one of the components of nucleic acids found in the nucleus of human cells. Many factors can affect a person's uric acid levels, such as genetics, lifestyle and physical activity. Coffee is one of the world's most popular drinks. The purpose of this research is determine the descriptionof blood uric acid levels in adult men who have the habit of drinking coffee with Robusta and Arabica coffee. The type of research used is descriptive analytic using cross- sectional analytic method. The population in this study were patients with gout who had a habit of drinking coffee at RSU Mayjen H.A Thalib Kerinci. The sample in this study was taken as many as 40 people with uric acid patien. Based on the research results, giving of the t test 0.178> 0.05 showed that there was no difference in uric acid levels between the types of Robusta and Arabica coffee. Keywords: Uric acid; coffee.